2011
DOI: 10.1096/fj.11-189415
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of HRas cysteine thiols by metabolic stress prevents palmitoylation in vivo and contributes to endothelial cell apoptosis

Abstract: Here we demonstrate a new paradigm in redox signaling, whereby oxidants resulting from metabolic stress directly alter protein palmitoylation by oxidizing reactive cysteine thiolates. In mice fed a high-fat, high-sucrose diet and in cultured endothelial cells (ECs) treated with high palmitate and high glucose (HPHG), there was decreased HRas palmitoylation on Cys181/184 (61±24% decrease for cardiac tissue and 38±7.0% in ECs). This was due to oxidation of Cys181/184, detected using matrix-assisted laser desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 38 publications
(41 reference statements)
1
52
0
Order By: Relevance
“…Our study provides the first example of endogenous ADP-ribosylation of small GTPases in mammalian cells, which has only been described during bacterial infection by ADP-ribosyltransferase toxins 13 . Interestingly, other studies have suggested that Hras Cys181 and 184 can also be oxidized and modified with glutathione during oxidative stress 47 , which suggests that these key Cys residues in the C-terminal hypervariable region of Hras are dynamically modified by S-fatty-acylation, S-glutathiolation, ADP-ribosylation and are highly sensitive to metabolic changes in cells. Our studies also provide another example of dynamic interplay between S-fatty-acylation and other posttranslational modifications 48 , which have been observed for example with S-palmitoylated and S-nitrosylated PSD-95 49 and suggested for other proteins from PTM-selective proteomic studies 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides the first example of endogenous ADP-ribosylation of small GTPases in mammalian cells, which has only been described during bacterial infection by ADP-ribosyltransferase toxins 13 . Interestingly, other studies have suggested that Hras Cys181 and 184 can also be oxidized and modified with glutathione during oxidative stress 47 , which suggests that these key Cys residues in the C-terminal hypervariable region of Hras are dynamically modified by S-fatty-acylation, S-glutathiolation, ADP-ribosylation and are highly sensitive to metabolic changes in cells. Our studies also provide another example of dynamic interplay between S-fatty-acylation and other posttranslational modifications 48 , which have been observed for example with S-palmitoylated and S-nitrosylated PSD-95 49 and suggested for other proteins from PTM-selective proteomic studies 50 .…”
Section: Discussionmentioning
confidence: 99%
“…They further proposed that direct competition from oxidative PTMs of the C-terminal reactive cysteines prevents H-Ras palmitoylation, leading to endothelial dysfunction. 6 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of PLM facilitates de-glutathionylation of Cys 46 of β1-subunit, with concomitant glutathionylation of PLM at Cys 42 [39], one of the cysteine residues in PLM that may also be palmitoylated. Thus the presence of PLM activates the pump in the sense that it is protected from oxidantinduced inhibition as a result of the reduced glutathionylation of Cys 46 .…”
Section: Competition Between Cysteine Post-translational Modifications?mentioning
confidence: 99%
“…Indeed, although the structural-sequence determinants of protein palmitoylation remain rather poorly characterized, it is well established that cysteine residues with low pK a values display high acylation rates in vitro [43], and low-pK a solvent-exposed cysteine residues are the very same sites that are also likely to be susceptible to glutathionylation. Competition between palmitoylation and oxidation/glutathionylation has been reported for proteins such as caveolin 1 [44], CD81 (cluster of differentiation 81) [45], H-ras and eNOS (endothelial nitric oxide synthase) [46]. Hence there may exist a set of proteins that are rendered insensitive to oxidation/glutathionylation by palmitoylation of key low-pK a cysteine residues, or even for whom palmitoylation and glutathionylation induce opposite effects in terms of changes in activity, as appears to be the case for the Na + pump.…”
Section: Competition Between Cysteine Post-translational Modifications?mentioning
confidence: 99%